Analysis Of The Availability Of Learning Facilities And Infrastructure To Improve Learning Interest Of Buddha Sunday School Students - Wirjawan Tjiptarahardja; Sutrisno Sutrisno; Mettadewi Wong (Jurnal Mamangan, 2023)
Students' learning interest at the Buddhist Sunday School had once declined, as reflected in the low attendance rate. After a change in management, the addition of facilities and improvement of infrastructure were carried out, which led to a significant increase in student attendance data. This study aims to analyze: (1) the causes of low student attendance prior to the improvement of facilities and infrastructure, (2) the current availability of learning facilities and infrastructure at SMB, and (3) the influence of learning facilities and infrastructure on increasing students' learning interest at SMB Vihara Theravada Buddha Sasana, Kelapa Gading, Jakarta. This research employed a qualitative approach with an instrumental case study method. Data were collected through direct observation, in-depth interviews with teachers and parents, and questionnaires distributed to SMB students. The study was conducted at SMB Vihara Theravada Buddha Sasana, Jakarta, with participants selected purposively according to research criteria. Data validity was ensured through source triangulation, while data analysis was carried out descriptively and qualitatively to understand changes in students' learning interest before and after the improvement of facilities and infrastructure at SMB. The results show that: (1) the decline in student attendance in 2022 was due to the adequate availability of facilities and infrastructure at SMB, (2) at present, the facilities and infrastructure at SMB are sufficient to support the learning process. The temple management provides facilities such as comfortable classrooms and various supporting equipment for religious learning and other activities, thus creating a conducive learning environment, and (3) after the improvement of facilities and infrastructure, the average student attendance in SMB activities increased significantly. The availability of complete facilities and infrastructure enables the implementation of diverse and interactive learning methods, which can stimulate and sustain students' learning interest. This increase in learning interest aligns with Maslow's hierarchy of needs theory and the four-phase model of interest development, in which the fulfillment of basic physical and safety needs, along with engaging learning stimulation, positively contributes to the growth of students' intrinsic motivation, which in turn impacts their learning interest. Therefore, the provision of adequate learning facilities and infrastructure is proven to play a significant role in enhancing students' learning interest at SMB.